The tadpole of the Swelled Vent Frog Feirana quadranus (Anura: Ranidae): Oral, chondrocranial and hyobranchial morphology - Huang, Min-Yi; Duan, Ren-Yan; Ji, Xiang (Zootaxa, 2014)
The genus Feirana includes three species of dicroglossid frogs, but much controversy on the classification and species content of this group still exists (Yang et al., 2011). Detailed information on tadpole morphology is of great importance in classifying amphibian species but, unfortunately, morphology of Feirana tadpoles remains poorly known. Here, we describe body shape, oral disc, chondrocranial and hyobranchial anatomy of Feirana tadpoles using the Swelled Vent Frog F. quadranus Liu, Hu & Yang, 1960 as a representative. This species is currently known to occur only in seven provinces (Gansu, Henan, Hubei, Shaanxi, Hunan, Shanxi and Sichuan) in the central part of China (Fei et al., 2005).